Accounting Education on Financial Literacy among University Students - Subedi, Purushottam (NPRC Journal of Multidisciplinary Research, 2025)
This study examines accounting education’s impact on financial literacy among Nepalese university students. A quantitative approach analyzed data from 385 students across multiple universities. Results show assessment practices were rated highest, followed by curriculum content and practical exposure. Financial literacy and teaching methods scored slightly lower. Correlation analysis confirmed strong positive links between educational components and financial literacy, with assessment showing the strongest relationship. Regression analysis revealed these factors explain 40.3% of financial literacy variance, with assessment and teaching methods as the strongest predictors. Findings highlight accounting education’s significant role in developing financial literacy and suggest improvements in teaching approaches and practical learning experiences.